PENDEKATAN URBAN ACUPUNCTURE MELALUI PROYEK PADEPOKAN SENI SRENGSENG - Juan Felix Harly Helga; Doddy Yuono (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
In Jakarta there are zones that have their respective land use functions, such as economic zones, government zones, cultural zones, green zones, etc. However, many people do not know about these zones, such as Jalan Merdeka Gambir as the government zone, and the Cikini area as one of the "cultural" zones. Apart from Cikini, there are many other areas which are cultural zones, but these "cultural" zones have been forgotten by the community due to the times. As a result, public interest in the cultures owned by the Indonesian state is reduced. The loss of public interest in culture will gradually make the culture that is owned disappear being consumed by the progress of time. Even though a country or region can be known by the public both at home and abroad because it has a unique culture. Therefore, this project aims to revive a culture that has faded, so that it can be remembered by the community and can continue to maintain cultural preservation. The method that the author uses is to collect information that can support the design title, such as collecting data on schools around the site that still maintain culture so that it can support the author's theme. The goal that the author wants to achieve is that the culture of the nation does not disappear, and also provides a place for people who are still interested in culture, so that culture does not disappear with time. Keywords:  culture; culture zone; progress of times Abstrak Di Jakarta terdapat zona-zona yang memiliki fungsi tata guna lahan masing-masing, seperti zona perekonomian, zona pemerintahan, zona budaya, zona hijau, dll. Namun, banyak masyarakat yang tidak mengetahui zona-zona tersebut, seperti jalan Merdeka Gambir sebagai zona pemerintahan, dan daerah Cikini sebagai salah satu zona “budaya”. Selain Cikini, masih terdapat banyak daerah lain yang merupakan zona budaya, tetapi zona “budaya” tersebut sudah dilupakan oleh masyarakat karena perkembangan zaman. Akibatnya, ketertarikan masyarakat terhadap kebudayaan-kebudayaan yang dimiliki oleh negara Indonesia berkurang. Hilangnya ketertarikan masyarakat terhadap kebudayaan lambat laun akan membuat budaya yang dimiliki hilang termakan oleh kemajuan zaman. Padahal suatu negara atau daerah dapat dikenal oleh masyarakat baik dalam maupun luar negeri karena memiliki kebudayaan yang unik. Oleh karena itu, proyek ini bertujuan untuk mengangkat kembali budaya yang sudah pudar, agar dapat diingat kembali oleh masyarakat dan dapat terus menjaga kelestarian budaya. Metode yang penulis gunakan dalah mengumpulkan informasi-informasi yang dapat mendukung judul perancangan seperti, mengumpulkan data sekolah-sekolah disekitar tapak yang masih melestarikan kebudayaan sehingga dapat mendukung tema penulis. Tujuan yang ingin diraih penulis adalah agar kebudayaan yang dimiliki bangsa tidak menghilang, dan juga memberikan wadah kepada para masyarakat yang masih tertarik terhadap budaya, sehingga budaya tidak menghilang termakan zaman.